Analysis of Working Capital Management, Institutional Ownership, and Asset Efficiency on Profitability: Role of Capital Structure on the Infrastructure Sector in the Indonesian Stock Exchange - Bogo Samudro, Galih; Mulyantini, Sri; Jubaedah, Jubaedah (Quantitative Economics and Management Studies, 2024)
This research examines the profitability of the sub-construction infrastructure sector within the building industry, as listed on the Indonesia Stock Exchange during the 2018-2022 period. The study aims to assess both the direct and indirect effects of working capital management, institutional ownership, and asset efficiency on profitability, with capital structure serving as an intervening variable. Utilizing panel data regression analysis, the research focused on a sample of seventeen companies from the building construction sub-sector listed on the Indonesia Stock Exchange over the specified period. The findings indicate that asset efficiency significantly influences profitability, whereas working capital management and institutional ownership do not. Additionally, capital structure is found to have no effect on profitability. Indirectly, neither working capital management nor institutional ownership, nor asset efficiency, when mediated by capital structure, show any impact on profitability.